If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-2+2)=6(x+3)
We move all terms to the left:
-3(-2+2)-(6(x+3))=0
We add all the numbers together, and all the variables
-(6(x+3))-30=0
We calculate terms in parentheses: -(6(x+3)), so:We get rid of parentheses
6(x+3)
We multiply parentheses
6x+18
Back to the equation:
-(6x+18)
-6x-18-30=0
We add all the numbers together, and all the variables
-6x-48=0
We move all terms containing x to the left, all other terms to the right
-6x=48
x=48/-6
x=-8
| 2(4h+3)+7=37 | | 8x+15=90 | | 7(-6+8)-8=7p-1 | | 16=4(m-1)-6(m-5) | | -3d-4+12d=32 | | 4x+6=-3x+6 | | v3+20=19 | | 4k^2-k-6=0 | | s6=s-3 | | m/3+7=-5 | | 7(x+63)=4(x-32) | | -3y+8=44 | | 26=50x+40 | | 5x-3=-26 | | H=-4.9t^2+8.8t+3 | | x^2+10x-27=-128 | | 1x-x=81924 | | 2h+25=75 | | -24=-8(9+y) | | 1+3j=-2 | | -20+4x=-8 | | -48=8(4p+1)-6(-1-5p) | | 5x^2+75=105 | | 5p+7-5=-18 | | -55=8(w+1)-w | | w-(+27)=-14 | | w/6+56=64 | | 6s-3s+4=19 | | -5/7c=-2 | | -2v+48=6(v+4) | | 6x+5=-8+4x+25 | | x2=9484 |